OC-073 Risks of Major Congenital Anomalies in Children Born to Women with Inflammatory Bowel Disease: a United Kingdom Population-Based Cohort Study. (4th June 2013) - Ban, L; Tata, L J; Card, T
Abstract : Introduction: Inflammatory bowel disease (IBD) affects women during the most fertile period of life. Previous studies of pregnant women with IBD on the risk of major congenital anomalies have inconsistent results due to diverse study populations and small sample sizes. Methods: We identified all singleton live births to women aged 15–45 between 1990 and 2010 from a large UK primary care database. We grouped children according to whether their mothers had IBD before childbirth or not and whether if so this was Crohn's disease (CD) or ulcerative colitis (UC). For children born to women with IBD, we also extracted records of prescriptions of 5-aminosalicylic acid, steroids and azathioprine in the first trimester of pregnancy. We calculated absolute risks of any major congenital anomaly and system-specific anomalies, and used logistic regression with a generalised estimating equation to compare risks. In women with IBD, we repeated the analyses to estimate the risks in children exposed or not exposed to medication. We adjusted the results for maternal age, year of childbirth, socioeconomic deprivation and maternal smoking. Results: Of 1, 703 children born to women with IBD and 384, 811 children born to women without IBD, 2.7% and 2.8% had records of any major congenital anomaly respectively. The risks of major congenital anomaly for CD and UC were 3.7% and 1.9% respectively. The adjusted odds ratio (AOR) of IBD with any major congenital anomaly was 0.98 (95% confidence interval [95%CI] 0.73–1.31). In children of women with IBD, 32.4% were exposed to 5-aminosalicylic acid in the first trimester and 12.3% and 8.7% to steroids and azathioprine respectively. There was no statistically significant increase in the risk of major congenital anomaly in children exposed to 5-aminosalicylic acid (AOR = 0.82, 95%CI 0.42–1.61), steroids (AOR = 0.48, 95%CI 0.15–1.50) or azathioprine (AOR = 1.27, 95%CI 0.48–3.39) in the first trimester compared with those unexposed. For system-specific anomalies, no increased risks in heart, limb or genital system were found. Conclusion: There are similar risks of major congenital anomalies in children born to women with and without IBD. No evidence of potential teratogenic effects of 5-aminosalicylic acid, steroids or azathioprine was found in this study. Previous guidance that women may be advised to continue these medications remains appropriate. Disclosure of Interest: None Declared